Variation of plumage patterns, geographic distribution and taxonomy of the Unicolored Blackbird (Aves: Icteridae) - Lopes, Leonardo Esteves (Zootaxa, 2017)
The Unicolored Blackbird Agelasticus cyanopus (Vieillot, 1819) is a marsh bird with four allopatric subspecies restricted to lowlands in South America east of the Andes. I conducted a taxonomic revision of the species based on analysis of external morphological characters of 288 study skins, including all types available. My revision shows that: 1) Leistes unicolor Swainson, 1838, is a senior synonym of A. c. xenicus (Parkes, 1966) and, therefore, the correct name of the taxon should be A. c. unicolor (Swainson, 1838); 2) the range of A. c. unicolor (Swainson, 1838) is much wider than previously thought, extending from the mouth of the Rio Amazonas to the state of São Paulo, in southeastern Brazil, where it intergrades with A. c. atroolivaceus (zu Wied-Neuwied, 1831); 3) A. c. atroolivaceus extends its range well beyond the coast of Rio de Janeiro, reaching the coast of São Paulo, the central part of Minas Gerais, Bahia and Espírito Santo; and 4) specimens attributed to A. c. beniensis are highly variable, so this name must be considered a subjective junior synonym of the nominotypical taxon. Under the Biological Species Concept, two broadly parapatric species should be recognized, A. cyanopus and A. atroolivaceus (including unicolor as a subspecies). Under the Phylogenetic Species Concept or the General Lineage Concept of Species, the best taxonomic treatment is to recognize three species: A. cyanopus, A. atroolivaceus, and A. unicolor.